Height and body composition determine arm propulsive force in youth swimmers independent of a maturation stage - Moura, T.; Costa, M.; Oliveira, S.; Barbosa Júnior, M.; Ritti-Dias, R.; Santos, M. (Journal of Human Kinetics, 2014)
The aim of this study was to examine the relationship between anthropometric variables, body composition and propulsive force in swimmers aged 9-17 years. Anthropometric characteristics (body height and mass, sitting height, arm span, arm muscle area and body composition) and the propulsive force of the arm (tethered swimming test) were evaluated in 56 competitive male swimmers. Tanner`s stages of genital maturation (P1-5) were used. The data analysis included correlations and multiple linear regression. The propulsive force of the arm was correlated with body height (r = 0.34; p =0.013), arm span (r = 0.29; p =0.042), sitting height (r = 0.36; p =0.009), % body fat (r = 0.33; p =0.016), lean body mass (r = 0.34; p =0.015) and arm muscle area (r = 0.31; p =0.026). Using multiple linear regression models, the percent body fat and height were identified as significant predictors of the propulsive force of the arm after controlling for the maturation stage. This model explained 22% (R2 = 0.22) of associations. In conclusion, the propulsive force of swimmers was related to body height and percent body fat.